Forest-related conflict: impacts, links and measures to mitigate - Koning, R.G. de; Capistrano, D.; Yasmi, Yurdi; Cerutti, P.O. (Rights and Resources Initiative, 2008)
Forest-based conflict is one of the major global challenges for the international forestry agenda together with poverty, climate change, conservation, and biofuels. In this paper, we will estimate the scope of the problem for people and forests, identify the role of forest rights and tenure as part of the cause of and solution to conflict, and project future challenges. We will recommend a set of actions that donors, govern¬ments, and civil society organizations should embark on to fight corruption, to tackle power imbalances, to clarify rights, to improve corporate responsibility, and to engage communities in resource management. Forest tenure and governance reform will not resolve the most violent conflicts that play out in forests around the world. However, forestry sectors can contribute to the creation of enabling environments for peace by preventing conflict escalation and by contributing to postconflict reconstruction. Engagements in structural forest-sector reform and forest-based investment are particularly needed in forest-rich and conflict-prone countries in the tropics. The ideas and projections included in this paper are preliminary and meant to stimulate reflection rather than to insist on particular conclusions.